MICROSTRUCTURE CHARACTERIZATION OF WCCo-Mo BASED COATINGS PRODUCED USING HIGH VELOCITY OXYGEN FUEL - Islak, Serkan; Kir, Durmus; Buytoz, Soner; Ozorak, Cihan; Akkas, Mehmet; Caligulu, Ugur; Yildirim, M. Mustafa (Pamukkale Univ, 2015)
The present study has been carried out in order to investigate the microstructural properties of WCCo-Mo composite coatings deposited onto a SAE 4140 steel substrate by high velocity oxygen fuel (HVOF) thermal spray. For this purpose, the Mo quantity added to the WCCo was changed as 10, 20, 30 and 40 wt. % percents. The coatings are compared in terms of their phase composition, microstructure and hardness. Phase compound and microstructure of coating layers were examined using X-ray diffractometer (XRD) and scanning electron microscope (SEM). XRD results showed that WCCo-Mo composite coatings were mainly composed of WC, W2C, Co3W3C, Mo2C, MoO2, Mo and Co phases. The average hardness of the coatings increased with increasing Mo content.
Keywords: Mo; WCCo; HVOF; Microstructure; Hardness